Information efficiency of the U.S. credit default swap market: Evidence from earnings surprises - Zhang, Gaiyan; Zhang, Sanjian (Journal of Financial Stability, 2013)
The credit default swap (CDS) market attracted much debate during the 2008 financial crisis. Opponents of CDS argue that CDS could lead to financial instability as it allows speculators to bet against companies and make the crisis worse. Proponents of CDS believe that CDS could increase market competition and benefit hedging activities. Moreover, an efficient CDS market can serve as a barometer to regulators and investors regarding the credit health of the underlying reference entity. We investigate information efficiency of the U.S. CDS market using evidence from earnings surprises. Our findings confirm that negative earnings surprises are well anticipated in the CDS market in the month prior to the announcement, with both economically and statistically stronger reactions for speculative-grade firms than for investment-grade firms. On the announcement day, for both positive and negative earnings surprises, the CDS spread for speculative-grade firms presents abnormal changes. Moreover, there is no post-earnings announcement drift in the CDS market, which is in direct contrast to the well-documented post-earnings drift in the stock market. Our evidence supports the efficiency of the CDS market.